Transformational Leadership in Educational Management: A Systematic Literature Review on Its Impact on Teacher Performance and School Quality - Solihun Solihun; Novan Ardy Wiyani (Universitas Nurul Jadid, 2025)
This study aims to systematically examine the impact of transformational leadership on teacher performance and school quality in contemporary educational contexts. Responding to the growing demand for improving educational quality and the fragmented nature of existing research, this study employs a Systematic Literature Review (SLR) approach following PRISMA guidelines. Data were collected from major academic databases, including Scopus, Web of Science, ERIC, and Google Scholar, focusing on empirical studies published between 2020 and 2025. A total of selected articles were analyzed using thematic analysis to identify key patterns and relationships. The findings indicate that transformational leadership consistently contributes to improving teacher performance, particularly in terms of motivation, job satisfaction, professional commitment, and instructional innovation. In addition, it plays a significant role in enhancing school quality by fostering a positive organizational culture, strengthening collaboration, and supporting continuous institutional development. However, the effectiveness of transformational leadership is influenced by contextual factors such as organizational readiness, leadership competence, and policy support. This study highlights that transformational leadership functions not only as an administrative approach but also as a strategic mechanism for sustainable educational improvement. The findings offer practical implications for school leaders and policymakers in developing adaptive and context-sensitive leadership practices.